Developmental stage of onset, poly-victimization, and persistence of childhood victimization: impact on adult well-being in a rural community-based study - Mitchell, Kimberly J. (Child maltreatment, 2020)
The current study examines the persistence of victimization and poly-victimization (i.e., count of multiple types of victimization) across various stages of development (ages 0?5, 6?12, and 13?18) and the related impact on adult well-being. Participants were 2,098 adults from the Appalachian region of three Southern states. Eighty-two percent of participants reported at least one type of victimization during childhood. Among adult victims, 22.6% reported one victimization in one developmental stage (i.e., one stage, but no poly-victimization), 45.8% reported one victimization in more than one stage (i.e., persistent victimization, but no poly-victimization), 20.5% reported multiple types of victimization in one stage (i.e., poly-victimization), and 11.2% reported multiple types of victimization at more than one stage (i.e., persistent poly-victimization). Results indicated a linear decline in subjective well-being, mental health, and number of healthy days as victimization becomes more persistent across childhood and more diverse in types (i.e., poly-victimization). Study findings provide support for models of victimization that take both developmental trajectories and poly-victimization into account.